Inventory of Catch Results in Seine Net Fishing Gear in Carocok Tarusan Coastal Waters, Pesisir Selatan Regency - Syaifudin, Muhammad; Yurleni, Yurleni; Lauura, Lauura Hermala Yunita; Mairizal, Mairizal; Besse, BC Monica Afriana; Putinur, Putinur (Department of Fisheries, Animal Science Faculty, Universitas Jambi., 2026)
The The waters of Carocok Tarusan Beach in Pesisir Selatan Regency have strong fisheries potential, with many coastal residents working as fishermen. This study aimed to inventory catches from seine net fishing gear and was conducted from July 20 to August 20, 2023, using a survey method with one 5 GT vessel and 10 landings. Data were collected through field observations and interviews. The results showed three species were caught, with tuna (Euthynnus affinis) as the main catch totaling 10,510 fish (1,251 kg; 77%), while anchovies (Stolephorus spp.) (128,100 fish; 173 kg; 11%) and peperek (Leiognathidae) (100,600 fish; 204 kg; 13%) were bycatch. The most frequent tuna sizes ranged from 282–305 mm and 338 359 mm, indicating tuna as the dominant catch in these waters.